Overall Stability Analysis of the Flying Bridge across Fish Ponds in Jinci Temple - Jinfang LI; Pengju HAN; Yijing AN; Lin CHAI; Chongen WANG; Xiangling BAI (Taiyuan Ligong Daxue xuebao, 2024)
Purposes As the "world's oldest overpass", the Flying Bridge across Fish Ponds in Jinci Temple highlights the cultural characteristics of ancient buildings in Shanxi. Methods In this paper, the compressive strength of the stone pillars of the Flying Bridge across Fish Ponds in Jinci Temple was tested with the rebound meter. AutoCAD software was used for three-dimensional modeling according to the mapping paper, and Abaqus finite element analysis software was used to simulate and analyze the overall stability under static load and seismic action. Findings The results show that under static action, for the Flying Bridge across Fish Ponds, the stress of the components is much less than the allowable value, and the settlement of the foundation is small and tends to be stable. Under the action of earthquake, the structural force is uniform and symmetrical, the top surface displacement is the largest, the third main stress of the stone column is mainly concentrated on the foot and the top of the column, and along the seismic wave loading direction, the oblique section develops, the stress is also less than the allowable value, and has good seismic stability. The results of this work can provide a reference for future conservation work of the Flying Bridge across Fish Ponds.